Validation of tsunami numerical simulation models for an idealized coastal industrial site. Issue 2 (3rd April 2022) - Watanabe, Masashi; Arikawa, Taro; Kihara, Naoto; Tsurudome, Chiaki; Hosaka, Koichi; Kimura, Tatsuto; Hashimoto, Takayuki; Ishihara, Fumitaka; Shikata, Takemi; Morikawa, Daniel Shigueo; Makino, Taiga; Asai, Mitsuteru; et al.
ABSTRACT: Numerous tsunami numerical models have been proposed, but their prediction accuracies have not been directly compared. For quantifying the modeling uncertainties, the authors statistically analyzed the prediction results submitted by participants in the tsunami blind contest held at the 17th World Conference on Earthquake Engineering. The reproducibility of offshore water level generated due to the tsunami with soliton fission significantly decreased when the nonlinear shallow water equation models (NSWE) was used compared to three-dimensional (3D) models. The inundation depth was reproduced well in 3D models. However, the reproducibility of wave forces acting on the structure and velocities over land was lower in 3D models than that in NSWE models. For cases where the impulsive tsunami wave pressure generated could not be calculated based on the hydrostatic assumption, the prediction accuracy of the NSWE models was higher than that of the 3D models. The prediction accuracies of both models were not improved at small grid-cell sizes. The NSWE model cannot simulate the short-wave component and vertical pressure distribution. Therefore, further developments in 3D models and smoothed particle hydrodynamics methods (SPH) are needed. The presented results contribute to the future development of tsunami numerical simulation tools.